Merkel Cell Carcinoma: Correlation of KIT Expression with Survival and Evaluation of KIT Gene Mutational Status - Andea, Aleodor A. (2010)
Merkel cell carcinoma is one of the most aggressive primary cutaneous malignancies. Since some Merkel cell carcinomas express the receptor tyrosine kinase KIT, we aimed to evaluate the correlation of KIT expression with outcome and the presence of activating mutations in the KIT gene in Merkel cell carcinoma. A total of 49 tumors from 40 patients with a diagnosis of Merkel cell carcinoma were identified of which 30 cases from 21 patients were used in the study. KIT expression was assessed by immunohistochemistry on formalin-fixed, paraffin embedded material. Cases were divided into low expressors (0-1+ staining intensity) and high expressors (2-3+ staining intensity). Direct sequencing of exons 9, 11, 13, 17, and 18 of the KIT gene spanning the extra-cellular, juxtamembrane and tyrosine kinase domains was performed from cases with high KIT expression. Thirty tumors from 21 patients were analyzed for KIT expression. High KIT expression was seen in 67% of the patients. Five-year survival rates in tumors expressing high versus low levels of KIT were 0% versus 57.8% respectively however, this dramatic difference did not reach statistical significance (p=0.07). A total of 4 point mutations were identified in 18 tumors analyzed. Two of these were silent mutations involving exons 17 and 18, and 2 involved intron 16-17. Two of the identified mutations may represent novel polymorphisms. Our work suggests a correlation between KIT expression and a worse prognosis in Merkel cell carcinoma patients, raising the possibility of an active role of this receptor in tumor progression and metastasis. We did not identify however, KIT activating mutations in any of the tumors analyzed.